Transfer of mRNA encoding recombinant immunoreceptors reprograms CD4+ and CD8+ T cells for use in the adoptive immunotherapy of cancer - Birkholz, K.; Hombach, A.; Krug, C.; Reuter, S.; Kershaw, Michael; Kämpgen, Eckhart; Schuler, Gerold; Abken, H.; Schaft, Niels; Dörrie, Jan (Gene Therapy, 2009)
Human T lymphocytes can be redirected with a new defined specificity by expression of a chimeric T-cell receptor (immunoreceptor) for the use in adoptive immunotherapy of cancer. Whereas standard procedures use retroviral gene transduction to constitutively express immunoreceptors in T cells, we here explored for the first time mRNA electroporation to achieve transient immunoreceptor expression, and thereby minimizing the risk of persistence of potential autoaggression. CD4+ and CD8+ T cells were efficiently transfected with immunoreceptors specific for ErbB2 and CEA. The immunoreceptor expression was transient with half-maximal expression at day 2 and no detectable immunoreceptor expression at day 9 after electroporation. Immunoreceptor-transfected T cells were specifically activated upon coincubation with ErbB2+ and CEA+ tumor cells, respectively, resulting in secretion of interferon-γ (IFNγ), interleukin-2 (IL-2), and tumor necrosis factor-α (TNFα). Furthermore, immunoreceptor-transfected CD8+ T cells specifically lysed ErbB2+ and CEA+ tumor cells, respectively. The RNA-transfected T cells retained their cytotoxic function after 2 days of activation and exhibited cytolytic activities like retrovirally transduced T cells. RNA electroporation of T cells thereby provides a versatile tool for transient immunoreceptor expression, which may be of advantage in avoiding the persistence of unintended autoaggression.
CRIS-Team Scopus Importer:2021-10-01